Protean Career Orientation In Tourism Public Service Agency Orientasi Karier Protean Pada Badan Layanan Umum Pariwisata (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
Currently, career self-management, also known as a protean career, is a phenomenon that companies must accept, especially since the boundaryless career paradigm has become ingrained in the minds of employees. This study uses career construction theory to prove the relationship between protean career orientation, innovation engagement, learning opportunities, and social contribution. By analyzing the questionnaire answers completed by employees at the Tourism Authority Board within the Ministry of Tourism of the Republic of Indonesia, it was found that learning opportunities and social contributions affected protean career orientation, while innovation involvement had no effect. The findings of this study show that in managing their careers independently, employees will improve their knowledge and skills in accordance with the work context, as well as promoting their reputation through contributions to the surrounding community.
Keywords: protean career orientation; tourism; public service agency